Effects of Dietary Phenylalanine and Tyrosine Supplements on the Chronic Stress Response in the Seabream (Sparus aurata) - Salamanca, Natalia; Moreno, Oscar; Giráldez, Inmaculada; Morales, Emilio; de la Rosa, Ignacio; Herrera, Marcelino (Frontiers in Physiology, 2022)
The increase of aquaculture production is associated with a growing interest in improving physiological status and welfare in fish. For this reason, the search for strategies for mitigating stress has been intensified, with one of these strategies being food supplementation with different amino acids (AA). The objective of this study was to evaluate the effects of dietary phenylalanine (Phe) and tyrosine (Tyr) supplements on the endocrine and physiological state of seabreams (Sparus aurata) subjected to chronic stress. The fish were stocked at 30 fish/tank in a recirculation aquatic system, fed one control diet and two diets supplemented with 5% Phe or Tyr for 90 days. Blood was drawn from 10 fish per tank every 30 days, and the weight and length were measured every 15 days. At the end of the experiment, length/weight of the fish were measured, and they were sacrificed for the extraction of blood, head kidney, liver, and brain. Classic plasma stress markers (glucose, lactate, proteins, and cortisol), as well as hormones derived from Phe and Tyr (adrenaline, norepinephrine, and dopamine) and the accumulation of AA were analyzed. Fish fed with diets supplemented with Phe or Tyr showed a reduction in various stress markers and physiological parameters. In addition, the stress condition favored a mobilization of AA toward the tissues, especially in supplemented diets, so this excess of AA could be used as an energy substrate to cope with stress.